Prediction in the religious sphere as a factor for ensuring the stability of social development: philosophical and religious studies analysis - Tytarenko, Vita Volodymyrivna (Relihijna svoboda, 2013)
The Milan edict 1700 years ago - in 313 proclaimed religious tolerance on the territory of the Roman Empire. How religious tolerance can exist in today's multiconfessional world, where there are processes of convergence of politics and religion, when the return of religion to the public arena and in world politics, in particular, raises the question of the peculiarities of its functioning. Securitization, and even more substantiated scenarios of the religious future? What, in fact, will mean deepening the process of globalization for the future of religion? Confrontation of two central trends in this process: the interpenetration of elements of different religions and their peculiar convergencealization? The resistance of unification and "borrowing", which will be accompanied by the growth of fundamentalist and conservative movements? As we see, there are a lot more questions than answers. At the same time, politicians and religious scholars respond somewhat differently to these and a number of other issues. The consensus of their forecasts is evidently the following - grounding on ever-increasing religious pluralism.